Foods, nutrients and food ingredients with authorised EU health claims. - Sadler, M. J. (Michele J.) (Woodhead Publishing in food science, technology, and nutrition., 2014)
Foods, Nutrients and Food Ingredients with Authorised EU Health Claims provides an overview of how health claims are regulated in the EU as well as detailed scientific and regulatory information about permitted health claims for particular types of foods and ingredients. Part one provides a background to the regulation of health claims in Europe. Part two focuses on authorised disease risk reduction claims, claims relating to children's development and health and proprietary claims. Part three sets out ingredients with permitted 'general function' claims, including choline, c.